2017
DOI: 10.1021/acs.cgd.7b00345
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Salts ofl-Carnosine: Combining a Natural Antioxidant and Geroprotector with “Generally Regarded as Safe” (GRAS) Organic Acids

Abstract: The potent natural hydrophilic antioxidant Lcarnosine has been reacted with a number of organic acids belonging to the "generally regarded as safe" (GRAS) group, resulting in the preparation of 11 new crystalline salts, which were characterized by X-ray powder diffraction and thermal analysis; the structures of six of them were determined from powder data, and one was fully characterized via single crystal data. The reaction with folic acid resulted in an amorphous folate salt, which was characterized by a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Even though mechanochemistry encountered serious limitations in the synthesis of these forms, it was shown to be appropriate, at least for the system with fumaric acid. The folate salt may be of particular interest, and therefore, its solubility was tested, showing that it has similar solubility to that of the commercial sodium folate [ 66 ].…”
Section: Developments Of Mechanochemistry In Portugalmentioning
confidence: 99%
“…Even though mechanochemistry encountered serious limitations in the synthesis of these forms, it was shown to be appropriate, at least for the system with fumaric acid. The folate salt may be of particular interest, and therefore, its solubility was tested, showing that it has similar solubility to that of the commercial sodium folate [ 66 ].…”
Section: Developments Of Mechanochemistry In Portugalmentioning
confidence: 99%
“…Acid-base interactions may lead to solubilities exceeding the pure low-solubility APIs [36]. Various studies have reported the enhancement achieved with formulations of acid-APIs combined with basic AA, such as arginine (ARG) and lysine (LYS), which have amino groups in their side chain (see Figure 2) [34].…”
Section: Introductionmentioning
confidence: 99%
“…These groups provide a basic reactivity toward the acidic functional groups of the selected API to form a salt. Regarding the formation of salts, according to Shemchuk et al [36], a difference of 2 or more between the pKb (base) and pKa (acid) values may determine salt formation in binary formulations since the probability of a proton transfer is high, and salt formation is expected [20,36]. Most commercially available tablet formulations stumble with the dissolution of FA since these exhibit different dissolution rates and low dissolution levels, failing to meet USP (US Pharmacopeia) requirements; this severely affects the therapeutic dose needed for specific supplementation required (e.g., pregnant women with NTDs history) [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Class II and IV quadrants of Biopharmaceutics Classification System (BCS) representing low solubility APIs can be improved by the design of molecular cocrystals and salts with generally recognized as safe (GRAS) coformers . The selection of GRAS coformer for a given API is guided by the Δp K a rule. We report newly synthesized salts and salt-cocrystals of the antibiotic drug pefloxacin (PEF) with improved physicochemical properties of high solubility and good stability.…”
Section: Introductionmentioning
confidence: 99%